ACOUSTIC-ELASTIC MEASUREMENTS OF ABSORBED DOSE USING POLYMER GEL DOSIMETER AS SOFT TISSUE-MIMICKING MATERIAL (REMUNOM, 2026)
Accurate absorbed dose dosimetry is a key factor for the effectiveness and safety of radiotherapy treatments, particularly when three-dimensional dose verification is required. In this context, polymer gel dosimeters stand out for their ability to record volumetric dose distributions, traditionally read using magnetic resonance imaging, a high-cost technique with limited clinical availability. This study investigates the applicability of an ultrasonic system as an alternative method for reading MAGIC-F polymer gel dosimeters used in radiotherapy. Initially, the system was calibrated using homogeneous gelatin-based samples with different concentrations, evaluating the response of ultrasonic velocity, attenuation coefficient, and elastic moduli. Subsequently, the methodology was applied to MAGIC-F gel samples irradiated with absorbed doses ranging from 0 to 40 Gy. Longitudinal ultrasonic velocity and attenuation coefficient were experimentally determined using the transmission–reception technique, while elastic moduli were estimated based on empirical relations supported by the literature. The results indicate an approximately linear attenuation behavior between 0 and 30 Gy, with a more pronounced variation at higher doses, suggesting distinct material response regimes. A systematic increase in mechanical stiffness with dose was also observed, as evidenced by the increase in Young’s modulus. These findings demonstrate the potential of ultrasound as a complementary tool for three-dimensional absorbed dose readout in polymer gel dosimetry.